Perception of youth on the retirement planning in Malaysia - Chai, Wen Yi; Chin, Siew Thoong; Lee, Swee Li; Lum, Seng Kit; Yeo, Teng Hui (2019)
This study aims to examine the relationship between the retirement planning and the three independents variables, which are income level, financial literacy and savings behaviour. Indirect effect on independent variables and retirement planning through demographic variables: age, gender and education level being examined. The targeted respondents referring to youth because aims to raise the awareness of retirement planning for the youth. Data in this research used is primary data and collected questionnaire from youth in thirteen states of Malaysia in order to understand their perspectives. The results retrieved are generated by 311 sets of the questionnaire from the respondents. Through the Partial Least Square (PLS-SEM) the results showed there is significant relationship between retirement planning and independent variables is. The results from the indirect effect of mediator variables towards independent variables and dependent variables showed that age and gender are significant relationship. However, the mediator variables of education level showed insignificant relationship to intermediate independent variables and dependent variables. This research will be benefits for the future researcher, government and the investment company to better understand the perception of youth towards the retirement planning in Malaysia.